Chemical composition and in vitro digestibility of indigenous pasture plants in different plant groups (Preliminary report) - Garmo, Torstein H. (Rangifer, 1986)
Several plant species from the following plant groups: ferns + horsetails, lichens, conifers (juniper), three leaves (Salix spp., Betula spp., Populus tremula, Sorbus aucuparid), heathers, grassens, rushes/sedges and forbs were collected in a mountain area of southerns Norway during the growing season from the 15th of June up to the 15th of September the years 1982 — 1984. Mean values (% of dry matter) of the different chemical constituents and in vitro dry matter digestibility of the different plant groups sampled throughout the growing season are given in Table 2. The mean crude protein content varied from 4.1% in lichens up to 17.5% in forbs; the crude fat were lowest for rushes/sedges (1.9%) and highest in juniper (13.3%); the crude fibre varied from 14.1% to 26.1% of three leaves and grasses, respectively; NFE showed lowest values for grasses (54%) and highest in lichens (74%). Ferns + horsetails contained the greatest (13.3%) and lichens the lowest (1.9%) amount of ash of the different plant groups. The levels of the macrominerals calcium, phosphorus, magnesium and potassium were all lowest in lichens (0.15; 0.09; 0.05; 0.13%) and highest in the forbs (1.19; 0.36; 0.37; 1.65%). Sodium levels varied from 0.029% in the heathers to 0.116% of ferns + horsetails. The forbs showed the highest mean in vitro dry matter digestibility (69%) and lichens the lowest (35%). However, the in vitro method (using sheep rumen inoculum) probably underestimates the dry matter digestibility of lichens, three leaves, juniper and heathers. Great variations in most of the chemical constituents as well as in vitro dry matter digestibility throughout the growing season for the different plant groups were demonstrated (Table 2). Keywords: nutrients, macrominerals, digestibility, livestock, wild ruminants, native pastures. Kjemisk innhald og in vitro fordøyelsesgrad av planter innan ulike plantegrupper frå fjellbeite (Førebels rapport). Abstract in Norwwegian / Samandrag: Ulike planteartar innan følgjande plantegrupper: karsporeplanter, lav, bartre (einer), lauvtre (vier spp., fjellbjørk, dvergbjørk, osp, rogn), lyng, gras, halvgras og urter vart innsamla i nokre fjellstrøk i Sør-Noreg gjennom veksttida frå ca. 15. juni til 15. september i åra 1982 — 1984. Middelverdiar (% av tørrstoffet) for plantematerialet innsamla til ulik tid i vekstsesongen og middel for heile vekstsesongen for dei ulike kvalitetsmåla er gitt i tabell 2. Protein-innhaldet varierte frå 4,2% i lav til 17,5% i urter; innhaldet av råfeitt var lågast i ha4vgras (1,9%) og høgast i einer (13,3%); trevleinnhaldet varierte frå 14,1% i blad av lauvtrea til 26,1% i gras; NFE vart funne å vera lågast i gras (54%) og høgast i lav (74%). Karsporeplantene hadde høgast (13,3%) og lav lågast (1,9%) oskeinnhald. Innhaldet av kalsium, fosfor, magnesium og kalium var lågast i lavprøvene (0,15; 0,09; 0,05; 0,13%) medan urtene i middel hadde høgast innhald av desse mineralstoffa av alle plantegruppene (1,19; 0,36; 0,37; 1,65%). Natrium-innhaldet varierte frå 0,029% i lyng til 0,116% i karsporeplantene. Fordyelsesgraden in vitro var i middel høgast for urtene (69%) og lågast i lavprøvene (35%). Fordøyelsesgraden (brukt vomsaft frå sau) er truleg sterkt underestimert for plantegruppene lav og lauv og tildels einer og lyng. Det vart også påvist større og mindre endringar gjennom veksttida for dei fleste kvalitetsmåla. Kasvien kemiallinen sisältö ja in vitro sulatusaste tunturilaidunten erilaisissa kasviryhmissä (Alustava raportti). Abstract in Finnish / Yhteenveto: Seuraavien kasviryhmien erilaisia kasvilajeja: kortekasveja, jäkäliä, havupuita (katajia), lehtipuita (pajulajeja, tunturikoivuja, vaivaiskoivuja, haapapuita, pihlajia), kanervia, ruohoja, saraheiniä ja yrttejä on kerätty muutamilla tunturialueilla Etelä-Norjassa kasvukautena n. 15. kesäkuuta 15. syyskuuta välisenä aikana vuosina 1982 — 1984. Kasviaineen keskiarvot (% kuiva-aineesta) kerättynä kasvuvaiheen eri aikoina ja keskiarvot koko kasvukautena eri laatumittauksissa on annettu taulukossa 2. Valkuaisaineen sisältö vaihteli 4.2%:sta jäkälässä 17.5% :iin yrteissä; raakarasvan sisältö oli alhaisin saraheinässa (1.9%) ja korkein katajissa (13.3%); kuitusisältö vaihteli 14.1 %:sta lehtipuun lehdissä 26.1 %:iin ruohoissä; typettömien uuteaineiden määrän havaittiin olevan alhaisin ruohoissa (54%) ja korkein jäkälissä (74%). Tuhkan sisältö kortteilla oli korkein (13.3%) ja/äkälillä alhaisin (1.9%). Jäkäläkokeiden kalsiumi-, fosfori-, magnesiumi- ja kaliumisisältö oli keskimäärin alhaisin (0.15; 0.09; 0.05; 0.13 %), kun taas yrteillä näiden kivennäisaineiden keskimääräinen sisältö oli korkein (1.19; 0.36; 0.37; 1.65 %) kaikissa kasviryhmissä. Natriumin sisältö vaihteli 0.029% :sta kanervissa 0.116% :iin kortekasveilla. Sulatusaste in vitro oli keskiarvoltaan korkein yrteillä (69%) ja alhaisin jäkäläkokeissa (35%). Sulatusaste (käytetty lampaan pötsinestettä) on ilmeisesti voimakkaasti ali-arvioitu jäkälissä ja lehdissä ja osittain katajissa ja kanervissa. Useimmissa laatumittauksissa oli myös osoitettu suurempia ja pienempiä muutoksia kasvuaikana.